A Secure and Scalable Authentication and Communication Protocol for Smart Grids - Muhammad Asfand Hafeez; Kazi Hassan Shakib; Arslan Munir (Journal of Cybersecurity and Privacy, 2025)
The growing adoption of smart grid systems presents significant advancements in the efficiency of energy distribution, along with enhanced monitoring and control capabilities. However, the interconnected and distributed nature of these systems also introduces critical security vulnerabilities that must be addressed. This study proposes a secure communication protocol specifically designed for smart grid environments, focusing on authentication, secret key establishment, symmetric encryption, and hash-based message authentication to provide confidentiality and integrity for communication in smart grid environments. The proposed protocol employs the Elliptic Curve Digital Signature Algorithm (ECDSA) for authentication, Elliptic Curve Diffie–Hellman (ECDH) for secure key exchange, and Advanced Encryption Standard 256 (AES-256) encryption to protect data transmissions. The protocol follows a structured sequence: (1) authentication—verifying smart grid devices using digital signatures; (2) key establishment—generating and securely exchanging cryptographic keys; and (3) secure communication—encrypting and transmitting/receiving data. An experimental framework has been established to evaluate the protocol’s performance under realistic operational conditions, assessing metrics such as time, throughput, power, and failure recovery. The experimental results show that the protocol completes one server–client request in 3.469 ms for a desktop client and 41.14 ms for a microcontroller client and achieves a throughput of 288.27 requests/s and 24.30 requests/s, respectively. Furthermore, the average power consumed by the protocol is 37.77 watts. The results also show that the proposed protocol is able to recover from transient network disruptions and sustain secure communication.